Indirect method to monitor the site size of sealed TEPCs. (February 2016) - Chiriotti, S.; Moro, D.; Conte, V.; Grosswendt, B.; Vanhavere, F.; Vynckier, S.
Abstract: Tissue equivalent proportional counters (TEPCs) can be used as radiation monitors in different radiation environments, including on board of a spacecraft or aircraft. Usually, the gas density of the counter is set to simulate site sizes of 1 μm or 2 μm. However, especially for sealed counters which should be operative for long time without being refilled, the gas density inside the counter could change significantly. The immediate consequence of density variations is a gas gain shift. This in turn is not a serious problem, because the gas gain can be measured and corrected by increasing the bias voltage. A more critical consequence of an increase of the density is that the shape of the microdosimetric spectrum changes, affecting the response of the detector. Consequently, this limits the reliability of sealed TEPC over time, especially because the gas pressure is not directly monitored. Therefore, the aim of this study is to propose an experimental procedure to estimate the TEPC sensitive-site size by performing two independent measurements, one in a gamma radiation field and the other one in a neutron field. The results show that it is possible to assess the site size of sealed TEPCs with an accuracy of 5%. Highlights: Estimation of TEPC sensitive-site size by performing two independent measurements. Two independent measurements in a gamma radiation field and in a neutron field. Ratio of the proton-edge and the electron-edge to estimate the gas density of TEPCs. It is possible to assess the site size of sealed TEPCs with an accuracy of 5%.